Resource potential of soft spring wheat varieties for the conditions of Western Siberia and Omsk region (analytical review) - Igor A. Belan; Lyudmila P. Rosseeva; Natalia P. Blokhina; Yuri P. Grigoriev; Yaroslava V. Mukhina; Natalia V. Trubacheeva; Lidia A. Pershina (Аграрная наука Евро-Северо-Востока)
The article is devoted to the review and analysis of varietal resources of soft spring wheat cultivated in the conditions of Western Siberia. For 2020, 261 varieties of this crop are included into the State Register of the Russian Federation, including 97 varieties (36.8 %) created by breeders of 15 institutions in the West Siberian region. In the Omsk region, depending on the climatic zone, the largest areas are occupied by the following varieties: mid-early – Omskaya 36 (242.16 thousand hectares), Pamyati Azieva (59.94 thousand hectares), Boevchanka (48.27 thousand hectares), Novosibirskaya 31 (36.3 thousand hectares); mid-season – Omskaya 38 (82.91 thousand hectares), OmGAU 90 (52.84 thousand hectares), Sigma (49.99 thousand hectares), Altaiskaya zhnitsa (35.2 thousand hectares); mid-late – Uralosibirskaya (145.72 thousand hectares), Melodiya (59.53 thousand hectares), Omskaya 28 (57.41 thousand hectares), Pavlogradka (67.31 thousand hectares), Element 22 (65.87 thousand hectares), Omskaya 35 (41.7 thousand ha). The joint creation of varieties with scientists from the Institute of Cytology and Genetics of the Siberian Branch of the Russian Academy of Sciences made it possible to use, along with collection samples and selection varieties, alloplasmatic introgressive lines of soft wheat carrying the cytoplasm of the cultivated barley Hordeumvulgare L. As the result, there have been developed Sigma, Uralosibirskaya 2, Ishimskaya 11 and Sakmara varieties with a high level of resistance to stem and leaf rust and a medium level to powdery mildew. Due to the massive increase of the leaf and stem rust, varieties with a high level of resistance to these pathogens have been created and recommended for cultivation – Omskaya 38, Sigma, Uralosibirskaya, Uralosibirskaya 2 and Element 22. In the main grain-growing soil-climatic territories of the Omsk region, 15 droughts have been recorded over the past 45 years. Thus, a method for in vitro testing of drought resistance has been developed. Varieties with increased drought resistance and high level of stem rust resistance (Omskaya 37, Omskaya 38, Uralosibirskaya and Omskaya 42) in drought-specific and epiphytotic 2020 exceeded the standard varieties by 0.90-1.74 t / ha in yield. Of special interest among new varieties are Omskaya 42, Uralosibirskaya 2, OmGAU 100, Stolypinskaya 2, Lider 80 and Omskaya 44. It is concluded that close cooperation with Institutes of the Russian Academy of Sciences and other scientific institutions is necessary in order to create varieties that combine increased productivity with resistance to unfavorable biotic and abiotic environmental factors.